Muhammadiyah Sufism: Building Students' Character and Faith Through Spiritual Education - Richway Richway; Romelah Romelah; M. Nurul Humaidi (JIE (Journal of Islamic Education), 2025)
This study explores the important role of Muhammadiyah Sufism in building character, optimising the purification of students' beliefs, and exploring the positive impact of the Islamic spirituality approach implemented by Muhammadiyah. The research method used involves qualitative data collection with a phenomenological approach involving semi-structured interviews, non-participant observation, and documentation with Muhammadiyah educational actors who have implemented the Sufi approach, namely the principal, teachers, and several students of Muhammadiyah Elementary School, Lahat. The data analysis technique uses the Miles and Huberman method, which focuses on the stages of data collection, data reduction, data presentation, and conclusion, for data validity techniques using triangulation. The research findings show that Muhammadiyah Sufism can strengthen the beliefs of Muhammadiyah Elementary School Lahat students, increase a deep understanding of Islamic teachings, and form positive characters in living their daily lives. This can be done through spiritual practices such as reading the Qur'an, sunnah prayers, dhikr, and sunnah fasting. This study also found that the implementation of Sufism in Muhammadiyah education helps students recognise and avoid practices inconsistent with pure Islamic teachings, such as excessive tawassul (circumambulation) and extreme meditation. Thus, Muhammadiyah Sufism education serves as a tool to purify faith and shape individuals with noble character and positive societal contributions. This study emphasises the importance of integrating Sufi values into the educational curriculum to create a generation that is intelligent, ethical, and capable of facing the challenges of the modern era. A limitation of this study is its limited focus on Muhammadiyah Elementary School in Lahat, which may reduce the generalizability of the findings regarding the implementation of Sufism in the broader context of Muhammadiyah education.